Analysis of Strain Aging of Steel Sheets by In Situ Electrical Resistance Measurement. (2020) - Nagano, Mai; Hayashi, Kotaro; Ueda, Masato
ABSTRACT: Observation of the dynamic interaction between dislocations and carbon atoms is important in steel design. Some steel materials are bake-hardened in several manufacturing processes. Solute carbons are known to segregate on dislocations; this hardens the steel even after low-temperature treatments. The purpose of this study was to develop a method of monitoring a series of microstructural changes in strain aging by in-situ measurement of the electrical resistance in low-carbon steel. In tensile deformation, elastic, Lüders, and uniform plastic deformations could be distinguished by monitoring the changes in electrical resistance. Electrical resistance rapidly increased in the plastic deformation region in the strain-aged specimen. Although the deformation stress hardly changed, the amount of lattice defects monotonously increased. These analyses provide useful information in steel design related to thermomechanical treatments of bake-hardenable steel.